2010
DOI: 10.1510/icvts.2009.212415
|View full text |Cite
|
Sign up to set email alerts
|

Barotraumatic oesophageal perforation with bilateral tension pneumothorax

Abstract: Barotraumatic oesophageal perforation with bilateral tension pneumothorax is extremely rare and this is a first case reported in the literature. The possibility of the oesophageal perforation due to high-pressure gas flow should be kept in mind and the standard of diagnosis is oesophagography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
2
3
0
1
Order By: Relevance
“…The highest PRR on patient safety culture composites was obtained on questions assessing teamwork (90.2%). In accordance with our study, teamwork received a higher PRR (76-94%) in other studies conducted in China [20], Turkey [21], Sweden [17] and Taiwan [18]. The reason for this high score might be due to the fact that pharmacy professionals' work in settings that have working stations near each other.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…The highest PRR on patient safety culture composites was obtained on questions assessing teamwork (90.2%). In accordance with our study, teamwork received a higher PRR (76-94%) in other studies conducted in China [20], Turkey [21], Sweden [17] and Taiwan [18]. The reason for this high score might be due to the fact that pharmacy professionals' work in settings that have working stations near each other.…”
Section: Plos Onesupporting
confidence: 89%
“…The results have also illustrated remarkable variations (45%-90.2%) in the PRR across the domains with mean overall PRR of 68.1%. The mean overall PRR was comparable with study findings reported from Sweden [17], Taiwan [18], United Arab Emirates [19] and Kuwait [6] (61.2%, 65%, 74.7%, and 83.8%, respectively).…”
Section: Plos Onesupporting
confidence: 87%
“…However, a delay in diagnosis until after the patient has eaten can lead to salivary leak into the neck tissues causing serious complications such as deep neck abscess or mediastinitis. For this reason a perforation with a delayed diagnosis has been shown to have high rates of mortality (16–75%) and morbidity (35%–66%) [ 7 ]. It is therefore essential to have a high index of clinical suspicion when a patient presents with barotrauma, odynophagia, and blood in pharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Chien et al concluded that optimal tool for the diagnosis of the esophageal perforation is the fluoroscopic esophagography. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair is difficult in case of delayed diagnosis, which is associated with high mortality rate (16%–75%) and morbidity rate (35%–66%). [6]…”
Section: Discussionmentioning
confidence: 99%